Quantifying Productivity Gains from Foreign Investment - Christian Fons-Rosen; Sebnem Kalemli-Ozcan; Bent E. Sorensen; Carolina Villegas-Sanchez; Vadym Volosovych (Tinbergen Institute, 2013)
We quantify the causal effect of foreign investment on total factor productivity (TFP) using a new global firm-level database. Our identification strategy relies on exploiting the difference in the amount of foreign investment by financial and industrial investors and simultaneously controlling for unobservable firm and country-sector-year factors. Using our well identified firm level estimates for the direct effect of foreign ownership on acquired firms and for the spillover effects on domestic firms, we calculate the aggregate impact of foreign investment on country-level productivity growth and find it to be very small.
urn:NBN:nl:ui:15-1765/39842
Keywords: E32; F15; F36; O16; 330; Multinationals; FDI; Knowledge Spillovers; Selection; Productivity; Auslandsinvestition; Multinationales Unternehmen; Produktivität; Schätzung; Welt